2010
DOI: 10.1007/s00702-010-0437-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the RAGE G82S polymorphism with Alzheimer’s disease

Abstract: The receptor for advanced glycation end-products (RAGE) has been implicated in several pathophysiological processes relevant to Alzheimer’s disease (AD), including transport and synaptotoxicity of AD-associated amyloid β (Aβ) peptides. A recent Chinese study (Li et al. in J Neural Transm 117:97–104, 2010) suggested an association between the 82S allele of the functional single nucleotide polymorphism (SNP) G82S (rs2070600) in the RAGE-encoding gene AGER and risk of AD. The present study aimed to investigate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…PCR products were digested with the respective restriction endonucleases (New England Biolabs, Inc., Ipswich, MA, USA), and the resulting fragments were separated on a 2.5% agarose gel containing 0.5 mg/mL ethidium bromide by electrophoresis at 100 V and visualized under UV light. Primer design was based on published sequences (Jurajda et al, 2002;Jin et al, 2005;Li et al, 2007;Checa et al, 2008;Kalousova et al, 2009;Daborg et al, 2010). The details of the primers, PCR conditions, restriction enzymes, and genotype configurations are shown in …”
Section: Selection and Genotyping Of Polymorphismsmentioning
confidence: 99%
“…PCR products were digested with the respective restriction endonucleases (New England Biolabs, Inc., Ipswich, MA, USA), and the resulting fragments were separated on a 2.5% agarose gel containing 0.5 mg/mL ethidium bromide by electrophoresis at 100 V and visualized under UV light. Primer design was based on published sequences (Jurajda et al, 2002;Jin et al, 2005;Li et al, 2007;Checa et al, 2008;Kalousova et al, 2009;Daborg et al, 2010). The details of the primers, PCR conditions, restriction enzymes, and genotype configurations are shown in …”
Section: Selection and Genotyping Of Polymorphismsmentioning
confidence: 99%
“…29 Recently, 2 independent studies showed an association between the 82Ser allele and the risk for Alzheimer disease. 2,30 Inter estingly, cognitive deficits 31 and neuronal atrophy 32 are suggested to be prevalent in patients with schizophrenia, and it is thus possible that the Gly82Ser polymorphism is a common denominator for cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…1 The ligands binding to RAGE include advanced glycation end products that arise during certain metabolic conditions and normal aging as well as amyloid fibrils, which make up the amyloid plaques seen in the brains of patients with Alzheimer disease. 2 Other well-studied ligands are the proinflammatory and neurotrophic members of the S100/ calgranulin family, S100A12 and S100B, which are secreted mostly by astrocytes in the central nervous system. 3 Recent studies have reported elevated serum and cerebrospinal fluid (CSF) levels of S100B in patients with schizophrenia, resulting in the hypothesis that astrocytes are either activated, damaged or dysfunctional in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several reasons may possibly account for the discrepancy between this study and ours: 1. Ethnic differences: Several studies reported that the genotype distribution of RAGE gene was quite variable among ethnic populations, especially between Caucasian and Chinese [45,46,47,48]. 2.…”
Section: Discussionmentioning
confidence: 99%